The Effect of Thyme (Zataria multiflora Boiss.) Decoction on Pregnancy in Rats - M Anvari; MH Dashti; F Zeinali; SM Hosseini-Bioki (Institue of Medicinal Plants, ACECR, 2011)
Background: Thyme is a plant in Labiata family which different species of this herb affects the menstrual cycle and therefore is avoided in high doses especially during the gestational period. Objective: Assessing the effect of thyme Decoction consumption in 2nd gestational week on placenta and fetus in rats. Methods: In this study 10 pregnant Wistar rats were randomly divided into 2 equal groups. Animals in test group received thyme Decoction in 2nd week of gestation. On 20th day of pregnancy, the placenta was removed and weighed. The number of live, dead or reabsorbed fetuses were recorded. All fetuses were weighed and stereomicroscopically examined for any morphological abnormalities in limbs, vertebral column, or head. Fetal height, fetal biparietal and placental diameters were also precisely measured. Results: There were no significant differences in the number of live fetuses, between 2 groups. No dead or reabsorbed fetuses and no morphological abnormalities were observed in live fetuses. The live fetuses in both groups showed the same weight, height and biparietal diameter but the length of tail in test group was longer than control group (p<0.05). The placental weight was approximately identical in 2 groups, but its diameter in test group was smaller than the control group (p<0.05). Conclusion: According to our findings, although the thyme Decoction consumption in 2nd gestational week did not lead to any abortion, due to its adverse effect on tail length and placental diameter, it is recommended that the thyme consumption be with precaution especially during the pregnancy.